UMPSA Rakan Muda Secretariat launched, KBS announced allocation of 1 Million for SRM IPT - Mimi Rabita, Abd Wahit (UMPSA, 2024)
GAMBANG, 13 February 2024 - The Ministry of Youth and Sports (KBS) continues to lead holistic and inclusive youth development.